Guyana : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guyana. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2022)
Following the pandemic-induced recession in 2020, economic growth recovered in 2021, with non-oil GDP growth reaching 4.6 percent, despite being negatively impacted by floods. Inflation increased markedly since 2021 owing to the floods and supply-side disruptions, as well as continually rising fuel and food prices. Oil production increased and will ramp up substantially over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Guyana